Greetings.
The answer is y = -2.
Explanation:
The equation is defined to solve for y-term. Our y is currently our subject at this point and needs to be solved.
We move -3 to another side and leave y as the subject of equation. Moving to another side will change the sign/operator to opposite.
Plus ---> Minus
Minus ---> Plus
Multiply ---> Divide
Divide ----> Multiply
![y-3=-5\\y=-5+3\\y=-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/srnyhcw2l42gkvu1egvp68jgunahj4wdgf.png)
Hope this helps! :)